2012
DOI: 10.1542/peds.2011-2308
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Maternal and Neonatal Staphylococcus aureus Colonization

Abstract: S aureus colonization (including MRSA) was extremely common in this cohort of maternal-infant pairs. Infants born to mothers with staphylococcal colonization were more likely to be colonized, and early postnatal acquisition appeared to be the primary mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 34 publications
8
80
3
1
Order By: Relevance
“…94,95 Colonization of S. aureus among pregnant women and its influence on the neonate and neonates born to mother with S. aureus colonization have been supported through the studies. 115 Occurrence of UTI among children has become a global problem and requires suitable measures to be addressed. Studies have demonstrated the extent of resistance exhibited the UTI pathogens among children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…94,95 Colonization of S. aureus among pregnant women and its influence on the neonate and neonates born to mother with S. aureus colonization have been supported through the studies. 115 Occurrence of UTI among children has become a global problem and requires suitable measures to be addressed. Studies have demonstrated the extent of resistance exhibited the UTI pathogens among children.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have provided sufficient amount of evidences to support the colonization of S. aureus among pregnant women and its influence on the neonate and neonates born to mother with S. aureus colonization and vulnerable to infection. 96,97 Demographic parameters like maternal, gestational age, gravidity, parity, socioeconomic condition and previous history of the infection can be vital and signifies the infection. 98 However some research studies feel that other pathogens of Staphylococcal genus are mistaken to be S. aureus but the other species of the genus are capable of causing the infection.…”
Section: 93mentioning
confidence: 99%
“…In the case of infants born at full term, a variety of factors have been evolutionarily selected to enhance colonization by beneficial microorganisms. Healthy term infants born vaginally are colonized by the maternal vaginal, intestinal, and skin microbiota shortly after birth [111]. Several factors will influence the diversity of the early microbiome.…”
Section: Box 3 Natural Microbial Colonization Of the Newborn Infantmentioning
confidence: 99%
“…Late-onset sepsis is noted to be four times higher in very low birth weight (VLBW) infants 66 . Imperative factors that are considered to increase the risk for neonates due to S. aureus colonization include breastfeeding, number of household members, prematurity, low birth weight and the duration of antibiotic or ventilator days [67][68][69] . Traditional antibiotic therapy, even though highly effective, has led to the emergence of antibiotic-resistant strains, such as methicillin resistant S. aureus (MRSA) 70 .…”
Section: Staphylococcus Aureus (S Aureus)mentioning
confidence: 99%
“…Traditional antibiotic therapy, even though highly effective, has led to the emergence of antibiotic-resistant strains, such as methicillin resistant S. aureus (MRSA) 70 . Communityacquired MRSA infections have been reported to occur in neonates and pregnant women or postpartum women, as a result of vaginal colonization of S. aureus during pregnancy 70 , with a prevalence of 0.5% -10% and in some areas, higher rates of colonization have been reported 64,68,71 . The factors that contribute to S. aureus rectovaginal colonization in pregnant women are not well understood, but it is believed to include black race 64,72 .…”
Section: Staphylococcus Aureus (S Aureus)mentioning
confidence: 99%